The Contribution of Mannose Binding Lectin to Reperfusion Injury after Ischemic Stroke - Morrison, Helena; Frye, Jennifer; Davis-Gorman, Grace; Funk, Janet; McDonagh, Paul; Stahl, Gregory; Ritter, Leslie (Current Neurovascular Research, 2011)
After complement system (CS) activation, the sequential production of complement products increases cell injury and death through opsonophagocytosis, cytolysis, adaptive, and inflammatory cell responses. These responses potentiate cerebral ischemia-reperfusion (IR) injury after ischemic stroke and reperfusion. Activation of the CS via mannose binding lectin (MBL)-initiated lectin pathway is known to increase tissue damage in response to IR in muscle, myocardium and intestine tissue. In contrast, the contribution of this pathway to cerebral IR injury, a neutrophil-mediated event, is less clear. Therefore, we investigated the potential protective role of MBL deficiency in neutrophil-mediated cerebral injury after IR. Using an intraluminal filament method, neutrophil activation and cerebral injury were compared between MBL-deficient and wild type C57Bl/6 mice subjected to 60 minutes of MCA ischemia and reperfusion. Systemic neutrophil activation was not decreased in MBL-deficient animals after IR. In MBL-deficient animals, cerebral injury was significantly decreased only in the striatum (p < 0.05). Despite MBL deficiency, C3 depositions were evident in the injured hemisphere during reperfusion. These results indicate that while MBL deficiency results in a modest protection of a sub-cortical brain region during IR, redundant complement pathway activation may overwhelm further beneficial effects of MBL deficiency during reperfusion.
Keywords: Complement